Self-similarity of surface heat transfer fields on a pre-heated rectangular plate in an obliquely impinging sonic jet. (February 2020) - Liu, Tianshu; Montefort, Javier; Stanfield, Scott; Palluconi, Steve; Crafton, Jim
Highlights: Self-similarity in the normalized heat transfer fields (surface temperature, heat flux and Nusselt number) is found for different pre-heated base temperatures in an obliquely impinging sonic jet. The relationship between the skin friction topology and heat transfer structures is explored. A theoretical analysis is given to elucidate self-similarity of heat transfer fields in this flow. Abstract: This paper presents an experimental study of the time-dependent surface temperature, heat flux and Nusselt number fields on a pre-heated, rectangular aluminum plate due to an obliquely impinging sonic jet at different total pressures. Surface temperatures are measured by detecting the luminescent emission from temperature sensitive paint. An analytical inverse solution of the one-dimensional time-dependent heat conduction equation is used to determine the heat flux from the temperature measurements. When normalized, the ensemble-averaged heat transfer fields (surface temperature, heat flux and Nusselt number) exhibit self-similarity (time-invariance) for different test conditions and therefore are found to exhibit a somewhat universal nature. A theoretical description of the self-similar behavior is presented for scaling experimental heat transfer data. Furthermore, the skin friction fields extracted from surface temperature and heat flux fields reveal generic topological structures of the flows.